A composite explosive based on supramolecular upy modification and a preparation method thereof
Patent Information
- Application Number
- CN202410595034.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-14
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-05-14
AI Technical Summary
[0005]针对现有技术存在的问题,本发明的目的在于提供一种基于超分子UPy改性的复合炸药及其制备方法,用于改善炸药与粘结剂界面作用弱、力学强度低的技术问题
[0021]本发明基于羟基与氰酸酯基的加成反应,将超分子UPy-NCO接枝到1,3,5-三氨基-1,3,5-三硝基苯炸药表面,一方面利用多重氢键作用形成高密度氢键网络;同时接枝分子链如同物理“锚点”,两种效应协同增强与粘结剂分子的相互作用,最终提升现有以1,3,5-三氨基-1,3,5-三硝基苯炸药为单质炸药的复合物力学强度。获得的TATB@UPy复合炸药,巴西强度能够最高为7.94MPa,压缩断裂强度最高为34.87MPa。
Smart Images

Figure CN118598720B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of mixed explosives and relates to a composite explosive based on supramolecular UPy modification and its preparation method. Background Technology
[0002] 1,3,5-Triamino-2,4,6-Trinitrobenzene is an energetic material with extremely low sensitivity to external stimuli, making it valuable in weapon charges. In practical applications, explosive charges are subjected to complex mechanical and thermal environments, placing higher demands on their mechanical properties. Exceeding the strength limit of the charge can lead to damage such as binder matrix cracking, interfacial debonding, and transgranular fracture of the explosive, becoming a key factor affecting its application. Improving the mechanical strength and toughness of explosive components can effectively enhance their adaptability to complex environments and reduce the risk of failure.
[0003] Explosive charges are mixtures, primarily composed of approximately 90 wt.% or more energetic crystals and polymeric binders. Common binders, due to their low surface energy, are unable to completely wet the surface of the explosive crystals, resulting in weak interfacial adhesion in composite explosives. Modifying the explosive surface can directly improve the interfacial compatibility between the explosive and the binder, thereby enhancing the mechanical properties of the composite explosive. By selecting suitable coupling agents / bonding agents with specific functional groups for pretreatment of the explosive crystals, a "bridge" is built between the explosive and binder molecules, effectively improving the wetting and spreading of the binder on the crystal surface, thus increasing mechanical strength and inhibiting creep. For example, TATB is modified with a silane coupling agent. The hydroxyl groups generated by the hydrolysis of the coupling agent form hydrogen bonds with the nitro groups of the explosive, improving the interfacial interaction. At the same time, some of the amino groups carried by the coupling agent can form chemical bonds with fluorinated polymers -F, enhancing the bonding effect (Energetic Materials, 2015, 23(2): 135-139; Mol. Simulat., 2013, 39(5): 423-427; RSC Advance, 2022, 12(31): 19946-19952). Some studies have reported that the explosive composite obtained by pretreating the surface of 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) with a neutral polymer bonding agent and then granulating it with a polymer binder has significantly improved the creep resistance and mechanical strength compared with the untreated explosive composite (RSC advances, 2015, 45(5): 35811-35820). Studies have shown that coupling agents / bonding agents can form hydrogen bonds with explosives, which is beneficial for improving interfacial interactions. However, coupling agents are prone to hydrolysis and are not suitable for water suspension granulation processes; while bonding agents have been shown to be selective for explosives and lack versatility.
[0004] How to design stronger hydrogen bonding on the surface of explosives to further improve the mechanical properties of composite explosives is a work with both potential and challenges. Supramolecular polymers can be defined as a class of macromolecular chain segments connected by reversible non-covalent bonds. In addition to the properties of traditional polymers, they also have the properties provided by dynamic bonding, including self-healing, stimuli reactivity and reversible adhesion. The non-covalent bond forms that constitute the cross-linked network of supramolecular polymers are diverse. Among them, hydrogen bonding has directionality and reversibility, and therefore has received widespread attention. In 1997, Meijer's research group first discovered a molecular polymer with four hydrogen bonds - 2-amino-4-hydroxy-6-methylpyrimidine (UPy) (Organic Letters, 2001, 3(24): 3887-3889; J.Am.Chem.Soc., 2000, 122(31): 7487–7493; Science, 1997, 278(5343): 1601–1604). The unique properties of the UPy subunit make it a special molecular building block. Zhao et al. used UPy for end capping to synthesize an adhesive material that exhibited a significant shear strength of 7.23 MPa and helped control debonding at low temperatures (Mater. Chem. Front. 2022, 6(12): 1658–1671). Some studies have used ureidopyrimidinone compounds with -NCO end groups, such as UPy-NCO, to modify nanocellulose and obtain nanocomposite films with excellent mechanical properties (Advances in Textile Technology, 2022, 8, 25-32). Patents disclose the application of UPy in water-based coatings, damping agents, and resins, which can effectively improve the specific properties of materials (CN108485474A, CN107987205A, CN111548510B). Patent CN113105607A discloses a self-healing polyester based on UPy quadruple hydrogen bonds and its preparation method, which prepares a polyurethane network with good mechanical properties and cyclic self-healing ability. However, the preparation method requires the addition of two chain extenders, and the process is relatively complicated. Summary of the Invention
[0005] To address the problems existing in the prior art, the present invention aims to provide a composite explosive based on supramolecular UPy modification and its preparation method, which improves the technical problems of weak interfacial interaction between explosives and binders and low mechanical strength. The above research demonstrates the enormous potential of UPy in material modification, and extending the idea of constructing hydrogen bonds with supramolecular UPy to the grafting modification of explosive surfaces will greatly expand its application areas.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solution:
[0007] A composite explosive based on supramolecular UPy modification, characterized by comprising the insensitive explosive 1,3,5-triamino-2,4,6-trinitrobenzene, a multi-hydrogen-bonded supramolecular polymer (UPy-NCO), and a binder (a copolymer of vinylidene fluoride and trichlorofluoroethylene in a 1:4 ratio, F... 2314 It is composed of (the same below) compound.
[0008] The particle size of the insensitive explosive 1,3,5-triamino-2,4,6-trinitrobenzene is (5-20) μm; the selected multiple hydrogen-bonded supramolecules are 2-(6-isocyanate hexylamine)-6-methyl-4-[h]-pyrimidinone (abbreviated as Upy-NCO-1) and 2-(6-isocyanate cyclohexylamine)-6-methyl-4-[h]-pyrimidinone (abbreviated as Upy-NCO-2), with molecular weights of 293.32 g / mol and 387.48 g / mol, respectively, and the addition mass ratio is (0.25~2) wt.%.
[0009] Multiple hydrogen-bonded supramolecular molecules are obtained through the following steps:
[0010] (1) 3.28 g of ureidylpyrimidinone (UPy) was added to 20 mL of 1,6-hexamethylene diisocyanate, heated to 100 °C and stirred for (12-14) h under a nitrogen atmosphere. The precipitate was precipitated with n-hexane and washed 3-4 times (150 mL / time), and dried under vacuum to obtain UPy-NCO-1;
[0011] (2) Add 2.0 g of ureidylpyrimidinone (UPy) to 20 mL of dicyclohexylmethane diisocyanate, heat to 100 °C and stir for (12-14) h, maintaining nitrogen atmosphere throughout. Precipitate with n-hexane and wash 3-4 times (150 mL / time), then dry under vacuum to obtain UPy-NCO-2.
[0012] The stirring speed was (300-600) rpm, the nitrogen flow rate was (0.1-0.2) mL / min, the vacuum drying temperature was (70-80)℃, and the drying time was (10-12) h.
[0013] A method for preparing a composite explosive based on supramolecular UPy modification, comprising the following steps:
[0014] (1) Surface pretreatment: The pH of the buffer solution was adjusted to 8.5 by dilute hydrochloric acid, dopamine hydrochloride was added and stirred evenly, and then 1,3,5-triamino-2,4,6-trinitrobenzene explosive powder was added, stirred, filtered, and vacuum dried to obtain pretreated explosive;
[0015] (2) Surface grafting: Dissolve the pretreated explosive from step (1) in a solvent, add supramolecular solution (UPy-NCO-1 or UPy-NCO-2), and then add (0.2-0.5) wt.% dibutyltin dilaurate. React in a nitrogen atmosphere for about (1-2) h, filter, wash 3-5 times, and vacuum dry to obtain UPy grafted explosive;
[0016] (3) Preparation of composite explosive: The explosive obtained in step (2) is added to deionized water, heated and stirred to form a mixed suspension, and then a binder solution with a concentration of (4-8) wt.% is added. The mixture is dispersed by water, bonded into granules, vacuum treated and dried to obtain a composite explosive with high-density hydrogen bonds.
[0017] The concentration of dopamine is (1-2) g / L, and the mass ratio of dopamine to insensitive explosive is (1 / 100-1 / 50).
[0018] The surface grafting solvent is one of acetone, dichloroethane, or chloroform. The multiple hydrogen bond supramolecular solution is prepared by adding UPy-NCO-1 to 2 to the solvent to form a (0.2 to 1) wt.% solution, and the mass ratio of the added supramolecular to the explosive is (0.25 to 2) wt.%.
[0019] The heating temperature is (50~80)℃, the stirring speed is (400~700)rpm, and the nitrogen flow rate is (0.1~0.2)mL / min.
[0020] Compared with existing technologies, the beneficial effects of this patent are reflected in:
[0021] This invention is based on the addition reaction of hydroxyl and cyanate groups, grafting supramolecular UPy-NCO onto the surface of 1,3,5-triamino-1,3,5-trinitrobenzene explosive. On one hand, it utilizes multiple hydrogen bonds to form a high-density hydrogen bond network; on the other hand, the grafted molecular chain acts as a physical "anchor," and these two effects synergistically enhance the interaction with binder molecules, ultimately improving the mechanical strength of existing composites using 1,3,5-triamino-1,3,5-trinitrobenzene explosive as the primary explosive element. The obtained TATB@UPy composite explosive exhibits a maximum strength of 7.94 MPa and a maximum compressive strength of 34.87 MPa.
[0022] This invention yields an explosive crystal / supramolecular composite with high-density hydrogen bonding, achieving a Brazilian mechanical strength of 7.94 MPa. Introducing supramolecular structures with multiple hydrogen bonds into explosives improves their mechanical properties and provides technical support for the application of composite explosives. Attached Figure Description
[0023] Figure 1 These are the structural formulas of UPy-NCO-1 and UPy-NCO-2 in this invention;
[0024] Figure 2 This is a schematic diagram of UPy-NCO-1 grafted onto the surface of the explosive in this invention;
[0025] Figure 3 This is a physical image of the composite explosive used in this invention. Detailed Implementation
[0026] The present invention will be further described below with reference to embodiments. These embodiments are merely some, not all, of the embodiments of the present invention. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the protection scope of the present invention.
[0027] For details, see Figures 1-3 Examples 1-3 illustrate the preparation method of composite explosives based on supramolecular UPy modification; Example 4 serves as a control group, using UPy to directly coat the surface of the explosive; Example 5 is a blank group, using only elemental explosives and F... 2314 A method for preparing energetic complexes from solutions; Example 6 serves as a control group, with an additional dopamine pretreatment step compared to Example 5.
[0028] Example 1
[0029] The pH was adjusted to 8.5 by adding 1 L of dilute hydrochloric acid dropwise to a buffer solution. Then, 1 g of dopamine hydrochloride and 100 g of 1,3,5-triamino-2,4,6-trinitrobenzene explosive powder were added. The mixture was stirred at 600 rpm for 6 hours, then filtered, washed, and dried to obtain the pretreated explosive. 50 g of the above explosive was added to 200 g of acetone. The reaction apparatus was placed in a 50°C water bath and stirred at 450 rpm for 5 minutes. A 0.5 wt.% solution of UPy-NCO-1 was prepared by dissolving UPy-NCO-1 in acetone. 0.2 g of dibutyltin dilaurate and 50 g of the UPy-NCO-1 acetone solution were added sequentially. The mixture was mechanically stirred at 500 rpm for 1 hour with a nitrogen flow rate of 0.12 mL / min. The mixture was filtered, washed three times with acetone, and dried under vacuum at 80°C to obtain the explosive grafted with UPy-NCO-1. Component analysis by high performance liquid chromatography showed that the content of 1,3,5-triamino-2,4,6-trinitrobenzene in the sample was 98.5%.
[0030] Take 48.22g of the above explosive and mix it with deionized water. Stir the mixture in a 60℃ water bath at 500rpm. Add 31.25g of 8% binder F dropwise. 2314 The solution was vacuum treated, and the suspension gradually agglomerated into particles, which were then dispersed by rinsing with water. After filtration and drying at 60°C, UPy-modified composite explosives (approximately 50g in total) were obtained.
[0031] The obtained composite was preheated to 120℃ and then pressed into a Φ20mm×20mm propellant column under a pressure of 120KN. The compressive fracture strength was tested to be 32.44MPa and the compressive fracture strain was 3.77%. The propellant column was also pressed into a Φ20mm×6mm propellant column. The Brazilian fracture strength was tested to be 7.89MPa, the Brazilian modulus was 7.86GPa, and the Brazilian fracture strain was 0.19%.
[0032] Example 2
[0033] The pH of a 1 L buffer solution was adjusted to 8.5 with dilute hydrochloric acid. 1 g of dopamine hydrochloride and 100 g of energetic crystals of 1,3,5-triamino-2,4,6-trinitrobenzene were added. The mixture was mechanically stirred at 600 rpm for 6 hours, then filtered, washed, and dried to obtain pretreated explosive. The explosive was then added to 500 g of acetone and sonicated for 1 minute to form a suspension. UPy-NCO-1 was dissolved in acetone to prepare a 1.0 wt.% solution. 0.35 g of dibutyltin dilaurate and 100 g of the UPy-NCO-1 acetone solution were added sequentially, all within a 50°C water bath. The mixture was mechanically stirred at 600 rpm for 2.5 hours with a nitrogen flow rate of 0.13 ml / min. The mixture was filtered and washed four times with acetone. It was then vacuum dried at 80°C to obtain the explosive grafted with UPy-NCO-1. Component analysis by high performance liquid chromatography showed that the content of 1,3,5-triamino-2,4,6-trinitrobenzene in the surface-grafted explosive was 98.2%.
[0034] Disperse 96.74g of surface-grafted explosive in deionized water, then add 83.33g of 6% binder F dropwise. 2314 The solution was mixed and stirred under vacuum at a water bath of 70°C and a rotation speed of 500 rpm, with water rinsing to disperse the mixture during the process. The final composite was rolled into granules. After filtration and drying at 60°C, the UPy-modified composite explosive (approximately 100 g in total) was obtained.
[0035] The resulting composite explosive was compressed into Φ20mm×20mm compressed charge and Φ20mm×6mm Brazilian charge under 120℃ and 120KN pressure. The compressive fracture strength was tested to be 34.87MPa, and the compressive fracture strain was 3.43%; the Brazilian fracture strength was 7.94MPa, the Brazilian modulus was 7.46GPa, and the Brazilian fracture strain was 0.22%.
[0036] Example 3
[0037] The pH of a 1 L buffer solution was adjusted to 8.5 with dilute hydrochloric acid. 2 g of dopamine hydrochloride was added, followed by 100 g of the energetic explosive 1,3,5-triamino-2,4,6-trinitrobenzene. The mixture was mechanically stirred at 550 rpm for 3 hours, then filtered, washed, and dried to obtain the pretreated explosive. 100 g of the explosive was added to 400 g of dichloroethane and sonicated for 1 minute to form a suspension. UPy-NCO-2 was dissolved in 1,2-dichloroethane to prepare a 1 wt.% solution. 0.45 g of dibutyltin dilaurate and 50 g of the UPy-NCO-2 dichloroethane solution were added sequentially, all within a 70°C water bath. The mixture was mechanically stirred at 550 rpm for 2 hours with a nitrogen flow rate of 0.14 mL / min. The mixture was filtered and washed three times with dichloroethane. Finally, it was vacuum dried at 70°C to obtain the explosive grafted with UPy-NCO-2. Component analysis by high performance liquid chromatography showed that the content of 1,3,5-triamino-2,4,6-trinitrobenzene in the surface-grafted explosive was 98.6%.
[0038] Disperse 96.15g of surface-grafted explosive in deionized water, then add 83.33g of 6% binder F dropwise. 2314 The solution was mixed and stirred under vacuum at a water bath of 70°C and a rotation speed of 450 rpm, followed by water dispersion to obtain granular composite powder. After filtration and drying at 70°C, UPy-modified composite explosive (approximately 100g total) was obtained.
[0039] The resulting composite explosive was preheated at 120℃ and compressed under a pressure of 120KN to form Φ20mm×20mm compressed explosive charges and Φ20mm×6mm Brazilian explosive charges. The compressive strength at break was tested to be 33.22MPa, with a compressive strain of 2.54%; the Brazilian explosive strength at break was 7.85MPa, with a Brazilian modulus of 8.18Pa and a Brazilian explosive strain of 0.19%.
[0040] Example 4
[0041] 49.5 g of energetic explosive 1,3,5-triamino-2,4,6-trinitrobenzene was added to 70 g of deionized water and stirred to form a suspension. UPy-NCO-1 was dissolved in acetone to prepare a 0.5 wt.% solution, and then 100 g of the UPy-NCO-1 acetone solution was slowly added dropwise to the suspension. The entire reaction was carried out in a 60°C water bath with mechanical stirring at 600 rpm for 1 h. Vacuum treatment was applied to evaporate the solvent, and the mixture was finally filtered and dried under vacuum at 60°C to obtain directly coated UPy-NCO-1 explosive. High-performance liquid chromatography (HPLC) analysis showed that the content of 1,3,5-triamino-2,4,6-trinitrobenzene in the modified explosive was 99.6%.
[0042] Take 47.69g of surface-coated explosive and disperse it in deionized water, then add 50g of 5% binder F. 2314 The solutions were mixed and subjected to vacuum treatment at 65°C in a water bath and 600 rpm, followed by water dispersion. The mixture was then filtered and dried at 60°C to obtain UPy-NCO-1 directly coated explosive molding powder (approximately 50g in total).
[0043] The molding powder was pressed into propellant columns with diameters of Φ20mm×20mm and Φ20mm×6mm under preheating at 120℃ and pressure of 120KN. The compressive strength was tested to be 32.6MPa, and the compressive strain at fracture was 2.63%; the Brazilian tensile strength was 7.55MPa, the Brazilian modulus was 8.36Pa, and the Brazilian tensile strain was 0.22%.
[0044] A comparison shows that, while maintaining a consistent content of 1,3,5-triamino-2,4,6-trinitrobenzene in the energetic complex (95% by mass), both Example 1 and this example introduce 0.5 wt.% UPy-NCO-1 as an interface modification. However, the compressive strength and mechanical strength of the drug column obtained in Example 1 are superior to those in this example. Therefore, introducing dopamine pre-modification and surface grafting of the multi-hydrogen-bonded supramolecular UPy is beneficial for improving interfacial interactions, thereby enhancing mechanical properties.
[0045] Example 5
[0046] This example serves as a blank control. 47.5g of untreated 1,3,5-triamino-2,4,6-trinitrobenzene was mixed with deionized water and stirred in a 70°C water bath at 550 rpm to form a suspension; approximately 62.5g of 8% F binder was slowly added dropwise. 2314 The solution is subjected to vacuum treatment, stirring, and rinsing with water. The suspension is then rotated into granules and dried at 65°C to obtain the energetic complex.
[0047] The above-mentioned energetic compound was pressed into a Φ20mm×20mm propellant column at 120℃ and 120KN pressure. The compressive strength at break was 28.16MPa and the compressive strain at break was 2.17%. The Φ20mm×6mm propellant column had a Brazilian fracture strength of 6.83MPa, a Brazilian modulus of 7.66GPa, and a Brazilian fracture strain of 0.18%.
[0048] The comparison shows that, while maintaining a consistent content of 1,3,5-triamino-2,4,6-trinitrobenzene in the complex (95% by mass), the compressive strength and Brazilian fracture strength of the explosive charges obtained in Examples 1-4 are superior to those in this example. Therefore, the introduction of dopamine pretreatment and supramolecular surface modification can enhance the interfacial interaction between the energetic crystals and the polymer binder compared to untreated explosives, thereby improving mechanical strength.
[0049] Example 6
[0050] The pH of a 1L buffer solution was adjusted to 8.5 with dilute hydrochloric acid. 1g of dopamine hydrochloride was added, followed by 100g of energetic crystals of 1,3,5-triamino-2,4,6-trinitrobenzene. The mixture was mechanically stirred at 600 rpm for 6 hours, then filtered, washed, and dried to obtain the pretreated explosive. High-performance liquid chromatography (HPLC) analysis revealed that the content of 1,3,5-triamino-2,4,6-trinitrobenzene in the pretreated explosive was 99.1%.
[0051] Disperse 95.86g of pretreated explosive in deionized water, and add 125g of 4% binder F dropwise. 2314 The solution is stirred to form a suspension, dispersed by water, and carried out in a 70°C water bath at 550 rpm with vacuum treatment. The composite explosive is rotated into particles, filtered, and dried to obtain the energetic composite.
[0052] The obtained energetic complex was pressed into a Φ20mm×20mm propellant column at 120℃ and 120KN pressure. The compressive fracture strength was 31.12MPa and the compressive fracture strain was 2.4%. The Brazilian fracture strength of the Φ20mm×6mm propellant column was 7.46MPa, the Brazilian modulus was 8.03GPa, and the Brazilian fracture strain was 0.20%.
[0053] In summary, while maintaining a consistent content of 1,3,5-triamino-2,4,6-trinitrobenzene in the energetic complex (95% in both cases), the composite explosive obtained in this embodiment exhibits superior strength and elongation compared to Example 5, indicating that dopamine pretreatment alone improves mechanical properties. The compressive strength and Brazilian fracture strength of the explosive charges obtained in Examples 1-4 are superior to those in Example 5 and this embodiment, demonstrating that introducing dopamine pretreatment followed by grafting with supramolecular UPy as an interfacial reinforcing agent synergistically enhances mechanical strength and improves the adaptability of the explosive charge.
[0054] The above embodiments are merely preferred embodiments of this patent, but the scope of protection of this patent is not limited thereto. It should be noted that, for those skilled in the art, without departing from the principles of this patent, based on the technical solution and patent concept of this patent, several improvements and modifications can be made, and these improvements and modifications should also be considered within the scope of protection of this patent.
Claims
1. A composite explosive based on supramolecular UPy modification, characterized in that, It is composed of insensitive explosive 1,3,5-triamino-2,4,6-trinitrobenzene, multiple hydrogen-bonded supramolecular molecules, and a binder; the selected multiple hydrogen-bonded supramolecular molecules are 2-(6-isocyanate hexylamine)-6-methyl-4-[h]-pyrimidinone and 2-(6-isocyanate cyclohexylamine)-6-methyl-4-[h]-pyrimidinone; the binder is a 1:4 copolymer of vinylidene fluoride and trifluorochloroethylene.
2. The composite explosive based on supramolecular UPy modification according to claim 1, characterized in that, The particle size of the insensitive explosive 1,3,5-triamino-2,4,6-trinitrobenzene is (5-20) μm.
3. The composite explosive based on supramolecular UPy modification according to claim 1, characterized in that... The molecular weights of 2-(6-isocyanate hexylamine)-6-methyl-4-[h]-pyrimidinone and 2-(6-isocyanate cyclohexylamine)-6-methyl-4-[h]-pyrimidinone are 293.32 g / mol and 387.48 g / mol, respectively.
4. The composite explosive based on supramolecular UPy modification according to claim 1, characterized in that, The multi-hydrogen-bonded supramolecular was obtained by the following steps: (1) Add ureidopyrimidinone to 1,6-hexanediisocyanate, heat to 100℃ and stir for (12~14)h, and treat under nitrogen atmosphere; precipitate with n-hexane and wash 3-4 times, and dry under vacuum to obtain 2-(6-isocyanate hexaneamide)-6-methyl-4-[h]-pyrimidinone; (2) Add ureidopyrimidinone to dicyclohexylmethane diisocyanate, heat to 100°C and stir for 12-14 h, maintaining nitrogen treatment throughout; precipitate with n-hexane and wash 3-4 times, then dry under vacuum to obtain 2-(6-isocyanate-cyclohexylamine)-6-methyl-4-[h]-pyrimidinone.
5. A composite explosive based on supramolecular UPy modification according to claim 4, characterized in that, In step (1), the ratio of ureidopyrimidinone to 1,6-hexamethylene diisocyanate is 1:(6-8); in step (2), the ratio of ureidopyrimidinone to dicyclohexylmethane diisocyanate is 1:(1-2); the stirring speed in both steps (1) and (2) is (300~600) rpm, the nitrogen flow rate is (0.1~0.2) mL / min, the vacuum drying temperature is (70~80)℃, and the drying time is (10~12) h.
6. A method for preparing a composite explosive based on supramolecular UPy modification, characterized in that, Includes the following steps: (1) Surface pretreatment: The pH of the buffer solution was adjusted to 8.5 by dilute hydrochloric acid, dopamine hydrochloride was added and stirred evenly, and then 1,3,5-triamino-2,4,6-trinitrobenzene explosive powder was added, stirred, filtered and vacuum dried to obtain pretreated explosive; (2) Surface grafting: Dissolve the surface pretreated explosive from step (1) in a solvent, add a multi-hydrogen bond supramolecular solution, the selected multi-hydrogen bond supramoleculars are 2-(6-isocyanate hexylamine)-6-methyl-4-[h]-pyrimidinone and 2-(6-isocyanate cyclohexylamine)-6-methyl-4-[h]-pyrimidinone, then add (0.2 ~ 0.5) wt.% dibutyltin dilaurate, react in a nitrogen atmosphere for (1 ~ 2) h, filter, wash 3 ~ 5 times, vacuum dry to obtain UPy grafted explosive; (3) Preparation of composite explosive: The UPy grafted explosive obtained in step (2) is added to deionized water, heated and stirred to form a mixed suspension, and then a binder solution with a concentration of (4~8) wt.% is added. The mixture is dispersed by water, bonded into granules, vacuum treated and dried to obtain a composite explosive with high-density hydrogen bonds. The binder is a copolymer of vinylidene fluoride and trichlorofluoroethylene in a 1:4 ratio.
7. The method for preparing a composite explosive based on supramolecular UPy modification according to claim 6, characterized in that, The concentration of dopamine is (1~2) g / L, and the mass ratio of dopamine to insensitive explosive is (1 / 100~1 / 50); the surface grafting solvent is one of acetone, dichloroethane or chloroform.
8. The method for preparing a composite explosive based on supramolecular UPy modification according to claim 6, characterized in that, In the preparation steps of the composite explosive, the heating temperature is (50~80)℃, the stirring speed is (400~700)rpm, and the nitrogen flow rate is (0.1~0.2)mL / min.
Citation Information
Patent Citations
Self-repairing polyurethane cross-linked network containing UPy side chain as well as preparation method and application thereof
CN113105607A
Method for designing and controlling microstructure of explosive based on supramolecular assembly and disassembly
CN102898258A
Preparation method of hydrogen bond self-assembly supramolecular photopolymerizable monomers
CN103483271A